2011
DOI: 10.1021/ac200229w
|View full text |Cite
|
Sign up to set email alerts
|

Isobaric Peptide Termini Labeling Utilizing Site-Specific N-Terminal Succinylation

Abstract: Recently, we introduced a novel approach for protein quantification based on isobaric peptide termini labeling (IPTL). In IPTL, both peptide termini are dervatized in two separate chemical reactions with complementary isotopically labeled reagents to generate isobaric peptide pairs. Here, we describe a novel procedure for the two chemical reactions to enable a cost-effective and rapid method. We established a selective N-terminal peptide modification reaction using succinic anhydride. Dimethylation was used as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(74 citation statements)
references
References 27 publications
2
70
0
2
Order By: Relevance
“…IPTL was performed according to Koehler et al 2011. 16 Briefly, purified and dried Lys-C peptide digests were suspended in 20 mM succinic anhydride (Sigma-Aldrich, Oslo, Norway) for control samples and in tetradeuterated succinic anhydride-d 4 (Larodan Fine Chemicals AB, Malmo, Sweden) for apoptotic samples in 50 mM sodium acetate.…”
Section: Lys-c Digestion and Isobaric Peptide Termini Labeling (Iptl)mentioning
confidence: 99%
See 1 more Smart Citation
“…IPTL was performed according to Koehler et al 2011. 16 Briefly, purified and dried Lys-C peptide digests were suspended in 20 mM succinic anhydride (Sigma-Aldrich, Oslo, Norway) for control samples and in tetradeuterated succinic anhydride-d 4 (Larodan Fine Chemicals AB, Malmo, Sweden) for apoptotic samples in 50 mM sodium acetate.…”
Section: Lys-c Digestion and Isobaric Peptide Termini Labeling (Iptl)mentioning
confidence: 99%
“…Protein identification and validation was performed using the IsobariQ software 17 including the force-find algorithm 16 to mine the spectra where Mascot failed to identify opposite sequences. No sequence suggestion below a Mascot ion score of 10 was allowed.…”
Section: Database Searches and Analysismentioning
confidence: 99%
“…Although IPTL improved the quantification accuracy compared to other reported MS/ MS level methods, the side reactions that are inherent in the multistep labeling can adversely affect quantification accuracy and dynamic range. 12 NeuCode SILAC 14 is another strategy based on subtle mass differences resulting from the mass defects of 12 C/ 13 C, …”
mentioning
confidence: 99%
“…The application of phenyl isocyanate labeling enabled relative quantitation of several styrene oxide adducts of human hemoglobin by LC-MS/MS [32]. Koehler et al [33] established a selective N-terminal peptide modification reaction using succinic anhydride and subsequently applied it to compare the proteome of HeLa cells incubated with S-trityl-l-cysteine to induce mitotic arrest and apoptosis. More recently, Yuan et al [34] reported a selective peptide derivatization approach to improve assay sensitivity for protein bioanalysis.…”
Section: Derivatizationmentioning
confidence: 99%